Literature Review of Achieving Sustainability through Circular Economy: Analysing Potential and Challenges for SMEs and Communities - A A Ngurah Bagus Aristayudha (International Journal of Economics, Business and Innovation Research, 2024)
The growing waste problem is a significant global issue, particularly in countries like Indonesia, which ranks second in waste production. This literature review explores the potential and challenges of implementing circular economy practices in Micro, Small, and Medium Enterprises (MSMEs) and communities to achieve sustainability. A circular economy framework promotes recycling, reuse, and extending product lifespans, aiming to reduce environmental impacts while enhancing resource efficiency. Despite the potential benefits, the transition to a circular economy faces hurdles such as limited awareness, insufficient infrastructure, and inadequate policy support. This study evaluates existing literature to understand these barriers and explore strategies for successful implementation. By analyzing the integration of circular economy principles in MSMEs and communities, this review aims to identify pathways to enhance economic, social, and environmental sustainability through effective circular practices.